TANGGUNG JAWAB BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) TERHADAP PERLINDUNGAN HUKUM PENGGUNA OBAT TRADISIONAL YANG MENGANDUNG BAHAN KIMIA OBAT (BKO) DIKOTA PEKANBARU - Yessi Seftiani; Hardi '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Traditional medicine is a material form of plant material, animal ingredients, mineral materials used for generations for the treatment based on experience. Under chapter seven versa two Indonesian republic’s health minister rules number seven in two thousand and twelve on the registration of traditional medicine, traditional medicines contain chemicals banned drugs that are isolated. Facts found in the field of twenty nine drug that contain chemicals traditional drug by a large hall food and drug regulatory Pekanbaru sold in drug stores pharmacies in town Pekanbaru.The purpose of this thesis, The first responsibility of a large hall drug and food-related Pekanbaru city folk remedies that contain medicinal chemicals market.The second major effort hall food and drug regulatory Pekanbaru city in tackling trafficking traditional medicines that contain chemicals, drug.This type of research is classified legal research sociological research on the effectiveness of the law in force, this study is a descriptive nature that is systematically describe, facts and characteristics of the object under study precisely.This research is conducted at the office of a large hall food and drug regulatory Pekanbaru, while the overall population and the sample is related to the problems examined in this study. Sources of data used, the primary data and secondary data consisting of primary legal materials, secondary, and tertiary, data collection techniques in this study with questionnaires, interviews, and a literature study and analysis of the data used is the qualitative analysisi and deductive.The final conclusion The first, a large hall responsibilities food and drug administration on drug related Pekanbaru town traditional drugs that contain chemicals that circulate in the city of Pekanbaru has a function that is pre market and post market. Second, a large hall attempts food and drug administration in tackling trafficking Pekanbaru traditional medicine that contains chemicals that extension, destruction of products, administrative sanctions, and confiscation without compensation. Advice authors, the first pre market and post market is further enhanced. Second, not only administrative but also criminal sanctions.Key word : Traditional medicine-BBPOM-Responsibility-Effort to cope